Identification of key genes and biological pathways in different parts of yak oviduct based on transcriptome analysis - Zhang, Jian; Pan, Yangyang; Zhao, Ling; Zhao, Tian; Yu, Sijiu; Cui, Yan (Frontiers in Veterinary Science, 2022)
The oviduct consists of three parts: infundibulum (In), ampulla (Am) and isthmus (Is). They have the same histological structure, but different physiological functions. In this study, transcriptomics was used to analyze mRNA in three parts of yak oviduct. The results showed that there were 325 up-regulated genes and 282 down-regulated genes between infundibulum and ampulla. Besides, there were 234 up-regulated genes and 776 down-regulated genes in the isthmus and ampulla, and 873 up-regulated genes and 297 down-regulated genes between infundibulum and isthmus. The expression of C3 in the infundibulum was significantly higher than that in ampulla and isthmus. The expression of FAU in isthmus was significantly lower than that in ampulla and infundibulum, and the expression of EEF1A1 in the ampulla was significantly higher than that in the ampulla and infundibulum. When infundibulum was compared with the ampulla and isthmus, it is found that the up-regulated genes were riched in lysosome, phagosome, staphylococcus aureus infection and leishmaniasis pathway. When isthmus was compared with ampulla and infundibulum, the up-regulated genes were focused on apoptosis pathway, oxidative phosphorylation, viral myocarditis pathway. When isthmus was compared with infundibulum and ampulla, the down-regulated pathways were protein processing in endoplasmic reticulum and endocytosis. Epstein-barr virus infection pathway was up-regulated pathway according to comparison between isthmus and infundibulum, which was also down-regulated pathway based on the comparison between isthmus and ampulla. Transcriptional misregulation in the Middle East pathway was the up-regulated enrichment pathway after the comparison between isthmus and ampulla, which was also down-regulated enrichment pathway based on the comparison between isthmus and infundibulum. ERBB2, JUP, CTNND1 and KRT7 were defined as the hub genes of yak oviduct. In this study, the results provide sufficient omics data for yak fertilization, which was also of great help in altitude medicine.